Disentangling fire, climate, forest structure, and land-use history interactions in Mexico's northern Sierra Madre - Meunier, Jed, author; Romme, William H., advisor; Knight, Richard L., advisor; Brown, Peter M., committee member; Fiege, Mark, committee member (Colorado State University. Libraries, 2012)
The 20th century was a period of profound changes in climate, land-use, forest structure, and fires throughout much of western North America and few montane forests continue to function under historical influences of climate variations and uninterrupted fire regimes. Yet, if we are to manage for resilient forests, understanding these linkages is critical and will depend on both pre-1900 and 20th century observations. My research takes advantage of a unique opportunity in northern Mexico to study forest and fire dynamics before a century of fire exclusion. My research documented a shift in climate - fire relationships in the late 19th century toward an overwhelming importance of antecedent moisture, unlike that seen previously for > 200 years. Tree recruitment peaks were tied to local processes, not broad-scale climate conditions. Antecedent wet conditions that promote fire occurrence suggests that in arid regions of the Southwest, anomalously wet years, still functioning under frequent fire occurrence, may further limit tree recruitment. The importance of fire induced mortality in shaping stand structure underscores the spatial variability of forests and helps explain even-age patches in forests as an artifact of patch survival of seedlings that recruit into the overstory.
Keywords: Aldo Leopold; climate; fire history; land health; Mexico; recruitment